People mover project (communication system) - Islam, Nafeez; Sakhawat, Navid Bin; Sharna, Sadia Tasneem; Manzoor, Ismot Ara (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.